Designing User Friendly Augmented Work Environments - Lahlou, Saadi (Computer Supported Cooperative Work, 2010)
Augmented environments - where objects are empowered by underlying information technology, are now installed in an ever-growing number of offices, public spaces and homes. However designing them to be usable and user-friendly remains a challenge. This book provides an overview and summary of the key research undertaken in augmented environments by some of the most prominent laboratories in the field worldwide (Stanford, Carnegie-Mellon, Fuji-Xerox Palo Alto, EDF R&D, Politecnico di Milano, Swedish Royal Institute of Technology, Russian Academy of Science, UC San Diego, University of Aachen). The book covers all relevant aspects of Augmented Environments from architecture to computer science and psychology. Most useful theories (activity theory, distributed cognition, cognitive attractors, perceived quality...) and design principles (COTS, semantic Rubicon, never-endingness...) as well as practical patterns for implementation are provided by the seminal authors themselves. With this overview, readers can benefit from the experiences of key researchers in the field to construct robust, efficient and user-friendly augmented environments. All those working in the field of human-computer interaction will find this book an invaluable reference source.